The far-zone behaviors of light waves on scattering from particulate medium with various distribution - Dai, Qihang; Xie, Zhongyuan; Pan, Xiaoning; Wang, Tao (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
The far-zone spectral density of light waves scattered on a particulate medium was discussed, and the influence of characteristics of the medium on the far-zone scattered spectral density was investigated. It is shown that the normalized spectral density of the scattered field is closely related with the structural characteristics of the particles collection, including the relative size of particles and the distribution information of particles in the collection. These results may provide potential application in the reconstruction of the structure information of particulate medium.
Optica Applicata, Vol. 52, 2022, nr 2, s. 273-282
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; weak scattering; particulate collection; spectral density